Las estrategias didácticas innovadoras contribuye al desarrollo del pensamiento creativos en niños/as de 3 a 5 años - Cabezas Carabali, Elsa Cristina (2013)
This project under the theme enunciated, it gives rise to the obvious need are teachers in the area of Early and Primary Education, the application in the classroom activities of innovative teaching strategies that allow the awakening of creative thinking children 3-5 years hence, lack of motivation and poor academic performance is evident in the daily educational work . Under a form of library research, field, descriptive and qualitative pedagogical describes problems caused by the lack of creative and innovative teaching resources applied in the Basic Education Development Project, which affects the development of the learning process, the instruments research was the survey which was carried out the manager of the institution, teachers and parents to assess the quality of the development of cognitive processes such as the development of creative thinking skills in this area and determine the significance of the implementation of strategic guidance counselor feature in the teaching-learning process, the presentation of activities and educational games easy, simple, accessible and affordable, with the approach of appropriate strategies, provide an opportunity to pass on the knowledge of the integral development the child both grafopásticas areas, language and communication, laterality, mathematical logic, in a fun, entertaining, motivating and especially efficient on a mutual learning in the classroom….